2021
DOI: 10.22271/tpi.2021.v10.i5c.6197
|View full text |Cite
|
Sign up to set email alerts
|

Agro-industrial waste as source of bioactive compounds and their utilization: A review

Abstract: Processing of horticultural goods produces a large amount of waste. Huge waste and losses in the food and processing industries are facing economic losses and environmental problems. Agro-industries byproducts can serve as important raw material for development of value added food products. The byproducts from fruits and vegetables can be used as unconventional alternate feed for animals which have best source of digestible nutrients and fulfill the gaps between demand and supply of feedstuffs. It is also used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Banana, apple, grape, and citrus peels have been studies as byproduct sources of phenolic compounds, flavan-3-ols, such as epicatechin and catechin, and flavanols, such as quercetin, and gallic, chlorogenic, and ferulic acids, which were found in different proportions (20–60 mg/100 g) depending upon the fruit from which they were obtained. These byproduct compounds showed antioxidant and anti-inflammatory properties. , In pomegranate peels, hydrolyzable tannins and phenolic acids have also been identified. Grape byproducts are low-cost, and this fruit contains resveratrol with several biological properties .…”
Section: Bioactive Agents Obtained From Agro-industrial Byproductsmentioning
confidence: 98%
See 4 more Smart Citations
“…Banana, apple, grape, and citrus peels have been studies as byproduct sources of phenolic compounds, flavan-3-ols, such as epicatechin and catechin, and flavanols, such as quercetin, and gallic, chlorogenic, and ferulic acids, which were found in different proportions (20–60 mg/100 g) depending upon the fruit from which they were obtained. These byproduct compounds showed antioxidant and anti-inflammatory properties. , In pomegranate peels, hydrolyzable tannins and phenolic acids have also been identified. Grape byproducts are low-cost, and this fruit contains resveratrol with several biological properties .…”
Section: Bioactive Agents Obtained From Agro-industrial Byproductsmentioning
confidence: 98%
“…Epidemiological studies show that the consumption of fruits and vegetables, rich in bioactive antioxidants, especially phenolic compounds, like flavonoids, may improve protective effects to human health and can reduce the risk of many diseases. 10 Agro-industrial byproducts are the most important potential sources of phenolic compounds; they are regarded as a possible source of a new food additives and include peels, seeds, skin peanut, and ripe fruits (Table 1). The potential uses of natural antioxidants as additives have been reported by many authors, who showed no significant differences with synthetic antioxidants.…”
Section: Bioactive Agents Obtained From Agro-industrial Byproductsmentioning
confidence: 99%
See 3 more Smart Citations